Knowledge, attitude and practices (KAP) of musculoskeletal disorders (MSDs) injuries in Malaysia electronics manufacturing industry - Nordin, Athirah Nadia (2016)
Musculoskeletal disorders (MSDs) are among the most frequently reported occupational disease and have depicted increasing exposure trend from electronics manufacturing sector. There are limited studies about Knowledge, Attitude and Practices (KAP) on MSDs from employer and employee perspectives. Hence, it is necessary to discover the underlying KAP factors in order to provide interventions to prevent MSDs. This study aims to develop an appropriate KAP instrument, identify the pattern of KAP on MSDs from employee and employer perspective, and to compare the level of KAP on MSDs among employee and employer. The instrument were developed in four phases; literature review, pilot test, expert review and reliability test. A total of 79 employee data was compared and validated with 164 SOCSO claims data. The highest frequency of employee self-reported body pain shows lower back, hip, shoulder and upper back are among the top. Of 88 employer, majority shows higher level of good knowledge, attitude and practice scores compared to employee. From employee perspective, Spearman’s correlation test shows education level correlate with knowledge and practice, gender and attitude, and age group and practice. From employer perspective, the correlation exist between education level and knowledge, and years of experience and practice. Multivariate analysis between KAP components for employee shows no correlation while for employer, there are relationship between attitude and practice, and knowledge and attitude. This study successfully developed an instrument to assess the current KAP levels of MSDs and compare them between employee and employer perspectives.